( c − a ) ( c − b ) ( 3 − 2 a ) ( 3 − 2 b ) + ( a − b ) ( a − c ) ( 3 − 2 b ) ( 3 − 2 c ) + ( b − c ) ( b − a ) ( 3 − 2 c ) ( 3 − 2 a )
Simplify the above expression for distinct numbers a , b , and c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using Lagrange-Interpolation . ( c − a ) ( c − b ) ( 3 − 2 a ) ( 3 − 2 b ) + ( a − b ) ( a − c ) ( 3 − 2 b ) ( 3 − 2 c ) + ( b − c ) ( b − a ) ( 3 − 2 c ) ( 3 − 2 a ) = 4 × ( c − a ) ( c − b ) ( 1 . 5 − a ) ( 1 . 5 − b ) + 4 × ( a − b ) ( a − c ) ( 1 . 5 − b ) ( 1 . 5 − c ) + 4 × ( b − c ) ( b − a ) ( 1 . 5 − c ) ( 1 . 5 − a ) Let f ( x ) = 4 × ( c − a ) ( c − b ) ( x − a ) ( x − b ) + 4 × ( a − b ) ( a − c ) ( x − b ) ( x − c ) + 4 × ( b − c ) ( b − a ) ( x − c ) ( x − a ) Then f ( x ) is the lowest degree polynomial that passes through the points ( a , 4 ) , ( b , 4 ) , ( c , 4 ) ,so f ( x ) = 4 , f ( 1 . 5 ) = 4
The expression is as follows:
S = c y c ∑ ( c − a ) ( c − b ) ( 3 − 2 a ) ( 3 − 2 b ) = c y c ∑ ( c − a ) ( c − b ) 4 ( 2 3 − a ) ( 2 3 − b ) = c y c ∑ ( x − z ) ( y − z ) 4 x y = 4 c y c ∑ ( x − y ) ( y − z ) ( z − x ) x y ( y − x ) = 4 × ( x − y ) ( y − z ) ( z − x ) x y ( y − x ) + y z ( z − y ) + z x ( x − z ) = 4 × x y 2 − x 2 y + y z 2 − y 2 z + z x 2 − z 2 x x y 2 − x 2 y + y z 2 − y 2 z + z x 2 − z 2 x = 4 Let x = 2 3 − a , y = 2 3 − b , z = 2 3 − c
You should know these:
( c − a ) ( c − b ) 1 + ( a − b ) ( a − c ) 1 + ( b − c ) ( b − a ) 1 = 0
( c − a ) ( c − b ) a + b + ( a − b ) ( a − c ) b + c + ( b − c ) ( b − a ) c + a = 0
( c − a ) ( c − b ) a b + ( a − b ) ( a − c ) b c + ( b − c ) ( b − a ) c a = 1
What's the cleanest way to see that these statements are true?
E.g. For the first, it is equivalent to multiplying throughout by ( a − b ) ( b − c ) ( c − a ) , which gives ( b − a ) + ( c − b ) + ( a − c ) = 0 .
As an aside, we also have
( c − a ) ( c − b ) c + ( a − b ) ( a − c ) a + ( b − c ) ( b − a ) b = 0
which follows by multiplying the first by a + b + c and subtracting the second.
( 1 ) = ( a − b ) ( b − c ) ( c − a ) ( b − a ) + ( c − b ) + ( a − c ) = 0
( 2 ) = − ( a − b ) ( b − c ) ( c − a ) ( b 2 − a 2 ) + ( c 2 − b 2 ) + ( a 2 − c 2 ) = 0
( 3 ) = ( a − b ) ( b − c ) ( c − a ) a b ( b − a ) + b c ( c − b ) + c a ( a − c )
We have that a b ( b − a ) + b c ( c − b ) + c a ( a − c )
= a b ( b − a ) − b c ( a − c ) − b c ( b − a ) + c a ( a − c )
= ( a b − b c ) ( b − a ) − ( b c − c a ) ( a − c )
= b ( a − c ) ( b − a ) − c ( b − a ) ( a − c )
= − ( a − c ) ( c − b ) ( b − a )
So ( 3 ) = ( a − b ) ( b − c ) ( c − a ) − ( a − c ) ( c − b ) ( b − a ) = 1
People are probably going to write a messy solution using cyclic sum and semplification. The problem has a numeric solution, so, as long as the denominators are not 0, one can put whatever numbers he want and still obtain the identity. Putting a=1, b=2, c=3, you get the solution, 4.
Of course, but it does not show that it works for all cases.
A slightly easier substitution is a = 2 3 ( b , c = 2 3 ), which gives 0 + 4 + 0 .
Of course, you're assuming that the answer is a constant.
Problem Loading...
Note Loading...
Set Loading...
Let x = 3 − 2 a , y = 3 − 2 b , and z = 3 − 2 c . Then a − b = 2 1 ( y − x ) , a − c = 2 1 ( z − x ) , and b − c = 2 1 ( z − y ) . Substituting these values into the expression gives
− 2 1 ( z − x ) ⋅ − 2 1 ( z − y ) x y + 2 1 ( y − x ) ⋅ 2 1 ( z − x ) y z + 2 1 ( z − y ) ⋅ − 2 1 ( y − x ) z x
which simplifies to
4 [ ( z − x ) ( z − y ) x y + ( x − y ) ( x − z ) y z + ( y − z ) ( y − x ) x z ] .
Using the identity ( z − x ) ( z − y ) x y + ( x − y ) ( x − z ) y z + ( y − z ) ( y − x ) x z = 1 , the expression further simplifies to 4 .